2014
DOI: 10.3897/bdj.2.e1078
|View full text |Cite
|
Sign up to set email alerts
|

Edaphic and light conditions of sympatric plant morphotypes in western Amazonia

Abstract: Here I present a dataset of edaphic and light conditions associated with the occurrence of sympatric morphotypes of Geonoma macrostachys (Arecaceae/Palmae), a candidate case study from Amazonia hypothesized to have evolved under ecological speciation. Transects were established in three lowland rainforests in Peru, and the abundance of each local morphotype of this species was recorded in a total area of 4.95 hectares. Composite soil samples and hemispherical photographs were taken along the transects were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…This may suggest that species of Geonoma are differentiated on resource axes other than edaphic conditions (e.g. light) (Chazdon, 1991;Roncal, 2014), which may also be consistent with our findings. In fact, Roncal et al (2012) found phylogenetic signal in some morphological characters of Geonoma species but not for characters with clear relationships to edaphic conditions.…”
Section: Phylogenetic Patterns Are Dominated By Small-sized Habitat Ssupporting
confidence: 90%
“…This may suggest that species of Geonoma are differentiated on resource axes other than edaphic conditions (e.g. light) (Chazdon, 1991;Roncal, 2014), which may also be consistent with our findings. In fact, Roncal et al (2012) found phylogenetic signal in some morphological characters of Geonoma species but not for characters with clear relationships to edaphic conditions.…”
Section: Phylogenetic Patterns Are Dominated By Small-sized Habitat Ssupporting
confidence: 90%
“…In addition to vertical light heterogeneity, the horizontal light heterogeneity in a forest also has a major influence on forest dynamics. In the understorey, horizontal light heterogeneity, which is strongly associated with the presence of canopy gaps (Roncal, 2014 ), influences the patterns of recruitment, growth, and survival of tree seedlings and saplings, even at the scale of a few square meters (Jin et al, 2018 ). In the canopy layer, horizontal light heterogeneity may be associated with crown development patterns because canopy trees tend to expand their crowns toward a better light environment (Muth & Bazzaz, 2002 ).…”
Section: Introductionmentioning
confidence: 99%